2012
DOI: 10.1111/j.1365-294x.2012.05512.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive sampling reveals circumpolarity and sympatry in seven mitochondrial lineages of the Southern Ocean crinoid species Promachocrinus kerguelensis (Echinodermata)

Abstract: Sampling at appropriate spatial scales in the Southern Ocean is logistically challenging and may influence estimates of diversity by missing intermediate representatives. With the assistance of sampling efforts especially influenced by the International Polar Year 2007-2008, we gathered nearly 1500 specimens of the crinoid species Promachocrinus kerguelensis from around Antarctica. We used phylogeographic and phylogenetic tools to assess its genetic diversity, demographic history and evolutionary relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 55 publications
9
90
4
3
Order By: Relevance
“…These also showed mostly circum-Antarctic distribution instead of regional partitioning. Similar findings were made for the crinoid Promachocrinus kerguelensis [Wilson et al (2007): restricted distribution range; Hemery et al (2012): circumpolar distribution range with extended data set]. Interestingly, analyses of a nuclear gene of C. megalonyx indicated that several of the mitochondrial clades do not represent distinct species as they had identical sequences for the otherwise highly variable nuclear internal transcribed spacer region (ITS; Dietz et al, 2015b).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…These also showed mostly circum-Antarctic distribution instead of regional partitioning. Similar findings were made for the crinoid Promachocrinus kerguelensis [Wilson et al (2007): restricted distribution range; Hemery et al (2012): circumpolar distribution range with extended data set]. Interestingly, analyses of a nuclear gene of C. megalonyx indicated that several of the mitochondrial clades do not represent distinct species as they had identical sequences for the otherwise highly variable nuclear internal transcribed spacer region (ITS; Dietz et al, 2015b).…”
Section: Introductionsupporting
confidence: 58%
“…Also, the radiation of the many Antarctic P. patagonica species very likely started in the late Pliocene and increased during the Pleistocene (last 2.5 myr). Such patterns have been reported before (e.g., Held, 2000;Page and Linse, 2002;Thornhill et al, 2008;Krabbe et al, 2010;Leese et al, 2010;Hemery et al, 2012;Dietz et al, 2015a,b) suggesting that over evolutionary time scales the Polar Front has not been an impermeable barrier to gene flow in general, though we did not observe across Drake Passage exchange in more recent clades of P. patagonica s.l. However, in view of the above-mentioned limitations of molecular clock calculations, we advise to use the divergence estimates made here with caution.…”
Section: Divergence Datescontrasting
confidence: 49%
“…Although benthic foraminifera do not show strictly pelagic stages in their life cycle, their propagules do seem to possess considerable dispersal potential Goldstein 2003, 2010). Their passive dispersal along coastal areas could be facilitated by the counterclockwise Antarctic Coastal Current (e.g., Hemery et al 2012). It does not explain, however, the considerable variability in genetic structure in certain benthic foraminiferal morphospecies.…”
Section: Dispersal Potential and Dispersal Patterns Among Antarctic Bmentioning
confidence: 99%
“…In many cases, cryptic species were discovered, e.g., among amphipods (Held 2003;Held and Wagele 2005;Lörz et al 2009;Baird et al 2011Baird et al , 2012, isopods (Raupach and Wägele 2006), ostracods (Brandão et al 2010), sea spiders (Mahon et al 2008), bivalves (Guidetti et al 2006;Linse et al 2007), sea stars (Janosik and Halanych 2010), crinoids (Wilson et al 2007;Hemery et al 2012), and benthic octopus (Allcock et al 1997;Strugnell et al 2009). By contrast, other organisms were confirmed to exhibit a circumpolar distribution, e.g., two species of shrimp (Chorismus anatrcticus and Nematocarcinus lanceopes) that recolonized Antarctic coastal waters following late Pleistocene climatic oscillations (Raupach et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al 2009). Her current work concentrates on molluscan phylogeny (Smith et al 2011) and Antarctic phylogeography (Hemery et al 2012).…”
mentioning
confidence: 99%